Contemporary medical, device, and surgical therapies for obesity in adults. Issue 10382 (1st April 2023) - Perdomo, Carolina M; Cohen, Ricardo V; Sumithran, Priya; Clément, Karine; Frühbeck, Gema
Summary: The goal of obesity management is to improve health. Sustained weight loss of more than 10% overall bodyweight improves many of the complications associated with obesity (eg, prevention and control of type 2 diabetes, hypertension, fatty liver disease, and obstructive sleep apnoea), as well as quality of life. Maintenance of weight loss is the major challenge of obesity management. Like all chronic diseases, managing obesity requires a long-term, multimodal approach, taking into account each individual's treatment goals, and the benefit and risk of different therapies. In conjunction with lifestyle interventions, anti-obesity medications and bariatric surgery improve the maintenance of weight loss and associated health gains. Most available anti-obesity medications act on central appetite pathways to reduce hunger and food reward. In the past 5 years, therapeutic advances have seen the development of targeted treatments for monogenic obesities and a new generation of anti-obesity medications. These highly effective anti-obesity medications are associated with weight losses of more than 10% of overall bodyweight in more than two-thirds of clinical trial participants. Long-term data on safety, efficacy, and cardiovascular outcomes are awaited. Long-term studies have shown that bariatric surgical procedures typically lead to a durable weight loss of 25% and rapid, sustained improvements in complications of obesity, although they have not yet been compared with new-generation highly effective anti-obesity medications. Further work is required to determine optimal patient-specific treatment strategies, including combinations of lifestyle interventions, anti-obesity medications, endoscopic and bariatric surgical procedures, and to ensure equitable access to effective treatments.